Implementation and Evaluation of Two Breast and Cervical Cancer Screening Events at a Student-Run Free Clinic - Mary Charleton; Hayley Dunlop; Jessica Sciuva; Cassidy Abdeen; Makena Ray; Gabriel Lee; Sreya Tummalapalli; Magdalene Adotey; Siddhi Shah; Robert Cooper; Caitlin Hull; Courtney Shihabuddin (Journal of Student-Run Clinics, 2025)
The Columbus Free Clinic (CFC), located in Columbus, Ohio (OH), is the largest interprofessional, student-run free clinic that provides medical and social services to underinsured individuals in OH. Despite the provision of in-house gynecologic services, only 20% of eligible patients had a recently documented cervical cancer screening, and only 1% had received a mammogram in the past 24 months. To address this need, two screening events providing cervical Pap tests, breast exams, sexually transmitted infection (STI) testing, and cholesterol screenings were held. The two screening events utilized different protocols to test the optimal operation of a large-scale gynecological screening event. Both events are described and compared to inform the development of similar initiatives at other free clinics nationwide. Outreach from the clinic was cited as a primary motivation for obtaining a Pap test amongst 60% of patients, and 89.5% of respondents said they would be “very likely to return” to CFC for future screenings. Student volunteers had increased knowledge of Pap tests and breast exams following these interventions. Screening events such as those outlined in this paper may help reduce the burden of breast and cervical cancer among underserved and under-insured patients at student-run-free clinics. They should be implemented in clinics with large populations with unmet screening needs.